KINERJA KEUANGAN USAHA MIKRO DAN KECIL NON KREDIT DI KABUPATEN KAMPAR - Djaimi Bakce; Fery Rizal (Indonesian Journal of Agricultural Economics, 2010)
The general objective of this paper is to analyze the financial performance of non-creditmicro and small enterprises (MSE) in Kampar regency. Specifically aimed to analyzethe financial performance of non-credit MSE of non-agricultural and agro-industrysectors compared with MSE non-agricultural sectors. The analysis of financial ratiosand analysis of economic value added are used. The main findings showed that: First,the financial performance of MSE in Kampar regency, both MSE non-agriculturalsectors and MSE agricultural and agro-industry sectors, which were analyzed using anumber of indicators and financial ratios economic value added indicates goodconditions. This is reflected from the calculation of their financial ratios and economicvalue added that indicates a value above the industry average. Second, the financialperformance of the aspects of liquidity and shows the activity of MSE non-agriculturalsectors are better than MSE agricultural and agro-industry sectors. While theprofitability aspect of MSE non-agricultural sectors are better than MSE agriculturaland agro-industry sectors. And third, either before tax or after tax, economic valueadded of MSE non-agricultural and agro-industry sectors are greater than MSE non-agricultural sectors. This reflects that MSE agricultural and agro-industry sectors havesubstantial opportunities to obtain income and improve their welfare as compared withMSE non-agricultural sectors. Therefore, in order to improve the financial performanceof MSE need to do the training and guidance from relevant agencies. Next to open andincrease access to MSE to formal financial institutions, need to apply the policydirection of government and formal financial institutions are more aligned to MSE. Inreal terms the policy in question is to reduce the number of requirements and simplifyprocedures in lending to MSE.